SCORES ON THE PRACTICE OF THE CULTURE OF PEACE AS A TOOL OF PEDAGOGICAL INTERVENTION IN THE MUNICIPAL EDUCATION NETWORK OF RECIFE - Cabral de Arruda Junior, Otacílio (Revista Gênero e Interdisciplinaridade, 2021)
This article is the result of an integrated action of school intervention developed in the Education Department of Recife City in one of the priority schools that presented a high rate of violence and low school flow. The present study was based on the principles of Pedagogy of Presence, authored by Antônio Carlos Gomes da Costa, whose main axis is the positive relationships created through the bonds of affection and respect established between the subjects in the school context. The pedagogical didactic strategies consisted of dialogue circle, pedagogical workshops and focus groups with themes about culture of peace. A great effort was made to generate the culture of mediation and peace to build respect and create affective bonds and collaborative citizen construction among the subjects of the school community. Therefore, the purpose of this work was to develop pedagogical actions that allow welcoming school environment, fostering respect, constructive interactions, and care for school equipment, valuing human relations and citizen education. It is initially punctuated that this work of school intervention has contributed significantly to germinate the practice of mutual respect relations between educator and student, basing the inventive and constructive intervention that is favorable to the personal and social development of children, adolescents, and young people.